2003
DOI: 10.1021/bi026727c
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Specificity Change of the Ovomucoid Third Domain of the Silver Pheasant upon Introduction of an Engineered Cys14−Cys39 Bond

Abstract: The ovomucoid third domain from silver pheasant (OMSVP3), a typical Kazal-type inhibitor, strongly inhibits different serine proteases of various specificities, i.e., chymotrypsin, Streptomyces griseus protease, subtilisin, and elastase. Structural studies have suggested that conformational flexibility in the reactive site loop of the free inhibitor may be related to broad specificity of the ovomucoid. On the basis of the structural homology between OMSVP3 and ascidian trypsin inhibitor (ATI), which has a cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…For example the number of amino acids between the first two cysteine residues is lower in invertebrates, resulting in a less flexible conformation causing the inhibitors to be more protease specific (Hemmi et al, 2003). These differences (and similarities) are excellently reviewed by Rimphanitchayakit (Rimphanitchayakit and Tassanakajon, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example the number of amino acids between the first two cysteine residues is lower in invertebrates, resulting in a less flexible conformation causing the inhibitors to be more protease specific (Hemmi et al, 2003). These differences (and similarities) are excellently reviewed by Rimphanitchayakit (Rimphanitchayakit and Tassanakajon, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Vol. 60,2003 Review Article 2431 also, there is an inhibitor with a single disulfide bond instead of the two typically observed among members of this family [65]. Worthy of note is that engineering of an additional disulfide bond near the reactive site of the silver pheasant third domain (Kazal inhibitor) left intact its potent inhibitory activity toward chymotrypsin, Streptomyces griseus proteases A and B, but almost abolished it toward pancreatic elastase [66].…”
Section: The Inhibitor Structurementioning
confidence: 99%
“…Introduction of the non‐natural disulfide into the reactive site loop has been applied to serpins19, but not to a small‐sized and compact inhibitor such as the ovomucoid third domains other than P14C/N39C. In the study elucidating the structural basis of the broad specificity of ovomucoid, we have unexpectedly found that P14C/N39C loses almost all inhibitory activity toward PPE, while it retains the potent inhibitory activities toward CHT, SGPA and SGPB17. Schematic representation of main chain folding of wild type OMSVP3 overlaid with that of P14C/N39C are shown in Figure 1B.…”
Section: Introductionmentioning
confidence: 97%
“…Double‐directed arrow points out two residues forming an engineered disulfide bond in P14C/N39C. Schematic representation of main chain folding of wild type OMSVP3 (red) overlaid with that of P14C/N39C (green) (B)17. Note that the six N‐terminal residues of wild type and P14C/N39C have been omitted from the models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation